Analysis Method for Reinforcing Circular Openings in Isotropic Homogeneous Plate-Like Structures Subjected to Blast Loading. (5th September 2018) - Mendes, Sebastian; Cao, Liling
Abstract : An analysis method is formulated to predict the peak bending stress concentrations around a small circular opening in an idealized isotropic homogeneous, linear elastic-perfectly plastic plate-like structure subjected to uniform blast loading. The method allows for the determination of corresponding concentrated bending moments adjacent to the opening for the design of reinforcement that can prevent the formation of localized plasticity around the opening during a blast event. The rapid formation and growth of localized plasticity around the opening can lead to a drastic reduction of the plate-like structure's local and global stability, which could result in catastrophic failure of the structure and destruction of the entity it is protecting. A set of elemental formulas is derived considering one-way and two-way rectangular plate-like structures containing a single small circular opening located where flexure predominates. The derived formulas are applicable for elastic global response to blast loading. Abaqus was employed to conduct numerical verification of the derived formulas considering various design parameters including material properties, plate dimensions, position of opening, and explosive charge size. The formulas demonstrate a good correlation with FEA albeit with a conservative inclination. The derived formulas are intended to be used in tandem with dynamic SDOF analysis of a blast load-structure system for ease of design. Overall, the proposed method has the potential to be applicable for many typical conditions that may be encountered during design.